EFFICIENCY IN INFRASTRUCTURE DEVELOPMENT - Adji Dwipawarman (NAROTAMA UNIVERSITY, Indonesia)
Infrastructure development is an important and vital aspect to accelerate the development process and support growth in Indonesia. Infrastructure also plays an important role as one of the economic drivers in Indonesia. This means that the rate of economic growth in Indonesia cannot be separated from the availability of infrastructure such as transportation and telecommunications. Therefore the construction of these facilities and services is the foundation of infrastructure development in Indonesia to support economic activities. Infrastructure development must be efficient and adapted to the conditions of each region, so that infrastructure development is appropriate to the needs of the region.